A study to determine factors that contributes to academic stress among students and their reactions towards the stressors / Saripah Abdul Latif, Razana Juhaida Johari and Zaihan Usman@Othman - Abdul Latif, Saripah; Johari, Razana Juhaida; Usman @ Othman, Zaihan (2004)
This study is extensively carried out to identify factors that contribute to academic stress among students and to ascertain the relationship between the levels of academic stress to academic performance of students. The findings identified eight significant factors that cause academic stress (stressors) out of forty possible stressors. The identification of students' reactions towards the stressors in this study perhaps, could facilitate the university in their effort to rectify the problem. From the analysis, it shows that 39.4% of Universiti Teknologi MARA Cawangan Kelantan (UiTMCK) students are having academic stress. Where as, the hypothesis testing shows that the levels of academic stress significantly influences the academic performance of students. Probing further it is ascertained that level of academic stress is negatively correlated to academic performance of students, though the association is rather weak. Such a study is significant to help the education planners and the management of Universiti Teknologi MARA (UiTM) in identifying strategies that could be adopted in an effort to create better learning conditions for students.